Stress e desempenho acadêmico na pós-graduação stricto sensu em Ciências Contábeis no Brasil - Rezende, Marise Santana de (2016)
Postgraduate admission is seen as an important transition in the student’s life, since this period can be understood as a process that involves a series of changes, pressures and charges that require the individual to adapt to the academic context. Given that some studies have indicated the postgraduate students, increasingly, as vulnerable to stress as a result of adjustments to these individuals are subject, this thesis main goal was to identify and analyze the relation between stress and academic performance perceived by students of stricto sensu graduate school in Accounting in Brazil. To carry out this research, we have selected a sample of 309 students (24.08% of the population) who were attending graduate school in Accounting. First, there was the descriptive statistics of the variables, and soon after conducted the Multiple Regression Analysis in two stages. The results of the first phase indicate that the variables "line of research," "to have a scholarship" and "program age", as well as concerns and difficulties inherent to the process, influence the stress level of the student. But in comparison to the results of the second regression testing, it was found that the variables prior to the academic performance and stress levels are significant in explaining academic performance. Thus, the results show the importance of monitoring the above identified stressors for the maintenance of student performance as well as prevent other problems arising from the drop in performance, such as evasion and other major damage.